2023
DOI: 10.3390/antibiotics12101539
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Acinetobacter baumannii Biofilm Formation by Terpenes from Oregano (Lippia graveolens) Essential Oil

Melvin Roberto Tapia-Rodriguez,
Ernesto Uriel Cantu-Soto,
Francisco Javier Vazquez-Armenta
et al.

Abstract: Acinetobacter baumannii is a nosocomial pathogen known for its ability to form biofilms, leading to persistent infections and antibiotic resistance. The limited effective antibiotics have encouraged the development of innovative strategies such as using essential oils and their constituents. This study evaluated the efficacy of oregano (Lippia graveolens) essential oil (OEO) and its terpene compounds, carvacrol and thymol, in inhibiting A. baumannii biofilms. These treatments showed a minimum inhibitory concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Moreover, these plant compounds combined with imipenem not only inhibited biofilm formation but also reduced the effective doses of the antibacterials required, which is in line with the strategy to combat bacterial resistance by using natural compounds that can disrupt biofilm formation and quorum sensing mechanisms [39,52,[70][71][72]. The combination treatments have shown potential for inhibiting biofilms by acting on different target sites and stages of biofilm development [27,[73][74][75][76][77][78][79][80][81][82][83]. This multipronged approach, targeting both the bacterial cell wall and disrupting biofilm integrity, holds the potential for more effective treatment strategies, providing an innovative direction in the fight against resistant bacterial infections.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Moreover, these plant compounds combined with imipenem not only inhibited biofilm formation but also reduced the effective doses of the antibacterials required, which is in line with the strategy to combat bacterial resistance by using natural compounds that can disrupt biofilm formation and quorum sensing mechanisms [39,52,[70][71][72]. The combination treatments have shown potential for inhibiting biofilms by acting on different target sites and stages of biofilm development [27,[73][74][75][76][77][78][79][80][81][82][83]. This multipronged approach, targeting both the bacterial cell wall and disrupting biofilm integrity, holds the potential for more effective treatment strategies, providing an innovative direction in the fight against resistant bacterial infections.…”
Section: Discussionmentioning
confidence: 66%
“…Biofilm formation in bacteria like P. aeruginosa and A. baumannii can significantly contribute to their resistance to antibiotics [27,39,64,65]. Recent research has highlighted the complexity of biofilm-associated antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly Tapia-Rodriguez et al . observed that oregano essential oils as well as terpene compounds carvacrol and thymol showed an ability to inhibit A. baumannii biofilm development and indicated that carvacrol reduced the structure even in 95% at concentration 0.15 mg/mL 74 . The abovementioned studies indicate that there is a possibility to also use essential oils in combating biofilm produced by A. baumannii strains.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that some essential oils may also exhibit mutagenic activity. The essential oil of Lippia graveolens has been demonstrated to exert an inhibitory effect on the formation of Acinetobacter Baumanni formation, affecting twitwching motility [17].…”
Section: Antibacterial Effectsmentioning
confidence: 99%